(untitled) (Comprehensive Journal of Science, 2025)
region), Gharyan (the mountainous region), and Sebha (the inland desert region). The Singer chart was used to identify the months of rest and work efficiency during the day, night, and full day. This was achieved by mapping the climatic elements of the Singer chart, namely minimum and maximum temperatures and relative humidity, over a thirty-year period extending from the beginning of January 1990 to the end of December 2022. The goal was to identify the months in which a comfortable climate prevails, allowing residents to feel comfortable in each region, and the months in which an uncomfortable climate prevails, causing residents to feel fatigued, uncomfortable, and unwilling to work. The study also aimed to identify the best stations and locations for comfort and work efficiency at the three different stations. By applying the chart, it was found that the best stations in the study area for rest, work efficiency, and production were, in order, Gharyan, due to the absence of bad months during the year. Then, Tripoli, with only August falling outside the ideal and relative comfort limits, and finally, Sebha, with five months. (May - June - July - August - September) are uncomfortable, i.e. outside the limits of ideal and relative comfort, and thus efforts and costs are doubled to create a comfortable atmosphere for its residents during the five months.